LITERATURE REVIEW: THE IMPORTANT SELF-HARM BEHAVIOR PREVENTION IN ADOLESCENTS (Proceedings OPTIMAL, 2024)
Deliberate self-harm behaviour is a major concern for health care systems. The prevalence, repetition and the potential for suicide make this one of the greatest challenges for staf. The method used in this writing is literature review which is a systematic method, uncovered and reproduced to carry out assistance, evaluation and synthesis of research works and ideas that have been produced by researchers and practitioners. Results:Twenty articles met criteria for inclusion. Between a third and one half of adolescents who self-harm do not seek help for this behaviour. Of those who seek help, results showed adolescents primarily turned to friends and family for support. Conclusion: It is important that the views of adolescents are incorporated into the design and delivery of youth-friendly services and that there is a focus on increasing awareness of the youth-orientated services that currently exist.